11+x=6(5x-3)

Simple and best practice solution for 11+x=6(5x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11+x=6(5x-3) equation:


Simplifying
11 + x = 6(5x + -3)

Reorder the terms:
11 + x = 6(-3 + 5x)
11 + x = (-3 * 6 + 5x * 6)
11 + x = (-18 + 30x)

Solving
11 + x = -18 + 30x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-30x' to each side of the equation.
11 + x + -30x = -18 + 30x + -30x

Combine like terms: x + -30x = -29x
11 + -29x = -18 + 30x + -30x

Combine like terms: 30x + -30x = 0
11 + -29x = -18 + 0
11 + -29x = -18

Add '-11' to each side of the equation.
11 + -11 + -29x = -18 + -11

Combine like terms: 11 + -11 = 0
0 + -29x = -18 + -11
-29x = -18 + -11

Combine like terms: -18 + -11 = -29
-29x = -29

Divide each side by '-29'.
x = 1

Simplifying
x = 1

See similar equations:

| 132+77t= | | -w^6+4w^4-4w^2+1=3.981 | | 60-24x= | | -3-3n=-3(2n-5) | | -15=r/5 | | -3z=8-3z | | 24x+64= | | Y=-4x^2+16x+20 | | 3a^3+3ab^2+2a^2b+2b^3= | | -(5-2)=5+2 | | 5x/8-3x/8 | | x*x-2x=3x+108 | | 5/6(-3/4) | | -42+-54= | | Y=-4x^2+16+20 | | 2x^4-x^3-6x^2=0 | | 4z+3z+6=90 | | 100-50d= | | x/y-1/5 | | x^2-2(x-1)=x^2(x-1) | | 6x+16-5x=-3-12 | | 7x/10-9=x/5+11 | | 3x+1=-4x-6x | | t/6=-10 | | -3(12+r)=-72 | | 42r-18= | | 2l*2w=300 | | 7x-5(3x+12)= | | 3(11r-13)= | | -3(12+2)=-72 | | 8+1w=3+2w | | 14-(6-3c)=4c*c |

Equations solver categories